Alpers- and MNGIE-like disease with disturbed CSF folate transport and an unusual mode of genetic transmission of POLG mutations: a case report. (2021) - Korinthenberg, Rudolf; Kirschner, Janbernd; Eckenweiler, Matthias, Robert Steinfel; Tatishvili, Nana Nino; Horvath, Rita
No abstract available